2009
DOI: 10.1111/j.1567-1364.2009.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement  of  thermo-tolerance in wineSaccharomyces cerevisiae  strains by a backcross approach

Abstract: During red wine fermentation, high temperatures may cause stuck fermentation by affecting the physiology of fermenting yeast. This deleterious effect is the result of the complex interaction of temperature with other physicochemical parameters of grape juice, such as sugar and lipid content. The genetic background of fermenting yeast also interacts with this complex matrix and some strains are more resistant to high temperatures than others. Here, the temperature tolerance of nine commercial starters was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
67
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 47 publications
4
67
0
1
Order By: Relevance
“…The correlation found between K and V max suggests that increasing K would also increase fermentative ability. Accordingly, previous data showed that a higher carrying capacity was associated with a higher CO 2 production rate in nearly isogenic S. cerevisiae strains (38), and Varela et al (66) showed that adding biomass reduced the time to achieve sugar consumption in slow fermentations. Using K as a selection criterion for AF would therefore increase the rate of fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation found between K and V max suggests that increasing K would also increase fermentative ability. Accordingly, previous data showed that a higher carrying capacity was associated with a higher CO 2 production rate in nearly isogenic S. cerevisiae strains (38), and Varela et al (66) showed that adding biomass reduced the time to achieve sugar consumption in slow fermentations. Using K as a selection criterion for AF would therefore increase the rate of fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we proposed a new strategy to preselect S. cerevisiae strains with good fermentative potential, based on their carrying capacity: measuring K can be achieved using a particle counter or a flow cytometer for numerous strains in a short time, allowing the evaluation of hundreds of poorly studied yeast strains available in collection centers. Strains displaying high carrying capacities could then enter traditional breeding programs involving crosses with well-characterized industrial strains, for example (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S2 in the supplemental material), suggesting that this strain would be a practical strain for industrial application. Enhancing fermentation output is the subject of intensive research on brewery yeasts (42,43). An obvious benefit of these efforts includes reduced production costs, for example, of bioethanol and alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Although tremendous progress has been made in genetic engineering to improve wine yeasts, genetically modified organisms (GMO) are still controversial. The use of molecular breeding techniques for unconsidered GMOs, such as intra-and inter-specific hybridization (Pérez-Través et al, 2012) or the classical backcross approach (Marullo et al, 2009), can prove very useful for introducing quantitative trait loci into a commercial strain background or for curing a genetic mutation.…”
mentioning
confidence: 99%